Axial length elongation in primary school-age children: a 3-year cohort study in Shanghai - Tao Li; Xiaodong Zhou; Bo Jiang (BMJ Open)
Objective To investigate the axial length (AL) elongation in primary school-age children during 3-year follow-up period and evaluate the associations of AL elongation with spherical equivalent (SE), AL at baseline, body height and weight.Design A 3-year observational cohort study from 2014 to 2017.Setting Jinshan Hospital of Fudan University in Shanghai.Methods A total of 452 children successfully completed their measurements in the 3-year follow-up period. The mean age of those children was 6.9±0.7 years, ranging from 6 to 8 years, and 217 (42.7%) were boys. AL was measured with an ocular biometry system. Refractive error was measured using an auto-refractor without cycloplegia.Results The mean changes of ALs were 0.27±0.28 mm, 0.52±0.40 mm and 0.89±0.51 mm over 1, 2 and 3 years, respectively. The mean changes of SEs were −0.27±0.80 D, −0.56±1.00 D and −0.95±1.41 D over 1, 2 and 3 years, respectively. Multivariate linear regression analysis revealed that mean change of AL was associated with mean change of SE at all points (all p<0.001). In addition, linear regression analysis revealed that AL elongation in the 3year follow-up period was associated with AL at baseline (R2=0.009, p=0.045).Conclusions AL elongation is relatively high in the primary school-age children in Jinshan District, Shanghai. Effect strategies are needed to control AL elongation.